Studies on raspy crickets: New Triaenogryllacris species (Orthoptera: Gryllacrididae) - Cadena-Castañeda, Oscar J.; Díaz, Carlos Julio Arango; Rodríguez, Nixon Oscar Parra; García, Alexander García (Zootaxa, 2020)
The genus Triaenogryllacris is redescribed and a key for identification of the species is provided. When dealing with observations of iNaturalist, accurate data about the distribution of T. triaena (the type species) are obtained, and three color forms are indicated: yellow, pink and green. Two new species are described here: T. diaena n. sp. and T. horaciotrianai n. sp., expanding the expected geographic distribution for the genus, thus recorded, from the Andean forests of Ecuador and Colombia’s three mountain ranges. Finally, the characters and distribution of Triaenogryllacris are discussed, contrasting with the other taxa described for the family Gryllacrididae.